2018
DOI: 10.1093/gerona/gly291
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-like Regulates Longevity and Glucose Metabolism via Insulin Signaling in Drosophila

Abstract: CD133, also called Prominin-1, is a biomarker for mammalian stem cells. It is involved in cell growth, development, and tumor biology. However, the function of CD133 at the organismal level has not been investigated. In this study, we found that prominin-like (promL) loss-of-function mutant flies show an extended life span and metabolic defects such as increased circulating carbohydrates, lipid storage, and starvation resistance. The messenger RNA expression levels of Drosophila insulin-like peptides (Dilps) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Moreover, these factors are not only associated with various ocular dystrophies but also involved in cancer development and regulation of stem cell maintenance and differentiation, cell growth, and metabolism ( Cehajic-Kapetanovic et al, 2019 ; Collison et al, 2019 ; Jamal et al, 2020 ; Lu et al, 2019 ; Priedigkeit et al, 2021 ; Wu et al, 2020 ). For example, in Drosophila, prominin (Prom), a homolog of human CD133, maintains mitochondrial function, regulates body size and weight, and influences animal longevity by controlling insulin and TOR signaling ( Ryu et al, 2019 ; Wang et al, 2019 ; Zheng et al, 2019 ). These functions resonate with the previously described functions for Dg in control of neuronal stem cell proliferation and differentiation, establishment of cellular polarity, maintenance of cellular homeostasis, and – at the organismal level – control of embryogenesis, stress response, adult animal metabolism, and longevity ( Kreipke et al, 2017 ; Kucherenko et al, 2010 ; Marrone et al, 2011b ; Shcherbata et al, 2007 ; Yatsenko and Shcherbata, 2014 ; Yatsenko et al, 2014a ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these factors are not only associated with various ocular dystrophies but also involved in cancer development and regulation of stem cell maintenance and differentiation, cell growth, and metabolism ( Cehajic-Kapetanovic et al, 2019 ; Collison et al, 2019 ; Jamal et al, 2020 ; Lu et al, 2019 ; Priedigkeit et al, 2021 ; Wu et al, 2020 ). For example, in Drosophila, prominin (Prom), a homolog of human CD133, maintains mitochondrial function, regulates body size and weight, and influences animal longevity by controlling insulin and TOR signaling ( Ryu et al, 2019 ; Wang et al, 2019 ; Zheng et al, 2019 ). These functions resonate with the previously described functions for Dg in control of neuronal stem cell proliferation and differentiation, establishment of cellular polarity, maintenance of cellular homeostasis, and – at the organismal level – control of embryogenesis, stress response, adult animal metabolism, and longevity ( Kreipke et al, 2017 ; Kucherenko et al, 2010 ; Marrone et al, 2011b ; Shcherbata et al, 2007 ; Yatsenko and Shcherbata, 2014 ; Yatsenko et al, 2014a ).…”
Section: Resultsmentioning
confidence: 99%
“…The w 1118 (BDSC 3605), Elav-Gal4 (BDSC 458) , and PAM-Gal4 (BDSC 41347) fly stocks were obtained from Bloomington Drosophila Stock Center (USA), and the UAS-promL RNAi (VDRC v51957) fly stock was obtained from the Vienna Drosophila Resource Center (Austria). The promL Δ7 and promL Δ19 mutant fly lines have been described previously ( Ryu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Drosophila , the prominin-like ( promL ) gene encodes the mammalian counterpart to CD133. The promL gene is involved in the maintenance of mitochondrial function ( Wang et al, 2019 ) at the cellular level, as well as the regulation of glucose metabolism, longevity ( Ryu et al, 2019 ), lipid metabolism, and body growth ( Zheng et al, 2019 ) at the organismal level. While metabolism and locomotion are closely related, the function of promL as a metabolic regulator in locomotion is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The subcellular localization of Prominin-1 suggests a possible role in cell membrane organization, but the precise functions of Prominin-1 have remained unclear. As described in this issue, Ryu et al (26) generated null mutations of the related Drosophila gene prominin-like, and found that the mutant flies had decreased expression of insulin-like peptides and increased life span. RNAi knockdown of prominin-like in the insulin-producing cells (IPCs) of the adult brain recapitulated these effects, consistent with the conclusion that prominin-like regulates Drosophila life span by regulating insulin-like signaling, thereby providing insight into the functions of this conserved gene family.…”
Section: Diet Interactions With Metabolism and The Mitochondriamentioning
confidence: 97%